2015
DOI: 10.1002/ajhb.22764
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of consanguineous marriages on autosomal recessive diseases in Tunisia

Abstract: This study reveals a variation in the excess risk linked to consanguinity according to the type of disorder, suggesting the potential of cryptic population substructure to contribute to disease incidence in populations with complex social structure like Tunisia. It also emphasizes the role of other health and demographic aspects such as mutation frequency and reproductive replacement in diseases etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 35 publications
1
12
0
6
Order By: Relevance
“…Among 19 Syrian GD patients, the consanguinity rate was 82%, which is very similar to our results [40], while among 425 Tunisian GD patients the consanguinity was (64.94%) [41].…”
Section: Discussionsupporting
confidence: 89%
“…Among 19 Syrian GD patients, the consanguinity rate was 82%, which is very similar to our results [40], while among 425 Tunisian GD patients the consanguinity was (64.94%) [41].…”
Section: Discussionsupporting
confidence: 89%
“…The emergence of an XP-G form that we identified here is also likely due to the high rate of consanguinity. Indeed, we have shown that consanguineous unions increase the risk of autosomal recessive diseases occurrence more than sixfold in the Tunisian population (Ben Halim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…2,4 In Tunisia, consanguinity is common. 5 However, little information exists on its impact on recessive disorders such as ARO. To our knowledge, only two Tunisian cases have been reported.…”
Section: Discussionmentioning
confidence: 99%